2017
DOI: 10.3892/etm.2017.4742
|View full text |Cite
|
Sign up to set email alerts
|

Significance of hydrogen sulfide in sepsis-induced myocardial injury in rats

Abstract: Sepsis-induced myocardial injury is a detrimental disorder for intensive care medicine due to its high rates of morbidity and mortality. Data suggest that nuclear factor (NF)-κB serves a critical role in the pathogenesis of myocardial injury. Hydrogen sulfide (H2S) serves an important role in the physiology and pathophysiology of regulatory mechanisms, particularly during an inflammatory reaction. However, the relationship between NF-κB and H2S in sepsis-induced myocardial injury is not well understood, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Therefore, an increase in IL-6 and a decrease in IL-10 signifies the onset of inflammation in response to CLP. These results are inconsistent with previous studies [23,24]. Furthermore, there was an increase in the protein expression of HMGB1 in the hearts of CLP-subjected rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, an increase in IL-6 and a decrease in IL-10 signifies the onset of inflammation in response to CLP. These results are inconsistent with previous studies [23,24]. Furthermore, there was an increase in the protein expression of HMGB1 in the hearts of CLP-subjected rats.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple studies have confirmed that an appropriate dose of H 2 S has cardiac protective effects (7,9,10), which may be associated with anti-apoptotic, anti-inflammatory and anti-oxidative mechanisms (11). A previous study by the present research team demonstrated that low doses of H 2 S are able to improve the cardiac dysfunction caused by sepsis (12); however, the specific mechanisms involved are not clear.…”
Section: Introductionmentioning
confidence: 74%
“…Rats (n=56) were randomly divided into 7 groups as follows: Sham group, underwent exposure of the cecum, but not ligation and perforation; sham + NaHS group, received the sham procedure and was administered a 2-ml/kg intraperitoneal administration of 8.9 µmol/kg NaHS 1 h following the surgery; sham + LY294002 group, underwent the sham procedure and was administered a 2-ml/kg intraperitoneal injection of 40 mg/kg LY294002 following the surgery; CLP group, treated with the CLP surgery; CLP + NaHS group, underwent CLP and was administered NaHS (dosage and method as in the sham + NaHS group); CLP + LY294002 group, underwent CLP and was administered LY294002 following the surgery (dosage and method as in the sham + LY294002 group); CLP + NaHS + LY294002 group, underwent CLP and was administered an intraperitoneal injection of NaHS and LY294002 at the aforementioned doses. The doses of LY294002 and NaHS were selected according to previous studies (5,12). Following the procedures, all the rats were free to drink and eat, and 12 h later they were anesthetized again.…”
Section: Methodsmentioning
confidence: 99%
“…In animal model of sepsis, the inhibition of H 2 S or its activation is proven beneficial to the hosts in terms of their survival and reduced tissue/organ injury, including myocardial injury, via improving neutrophil infiltration, K + ATP channel activation, reducing TNF-α, and increasing IL-10 levels 282284. The CLP-induced sepsis in mice causes a significant increase in the plasma level of H 2 S along with its synthesis in the liver 8 hours post-CLP 282.…”
Section: Inflammasomes In the Immunopathogenesis Of Sepsismentioning
confidence: 99%